(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the effectiveness of using an electronic publication (en) for "self-education" for schoolchildren based on computer technologies. The study highlights the development of students’ logical thinking and the consolidation of knowledge through the "self-education" electronic publication (EP) in problem-solving. Problems in traditional teaching methods (time constraints, low motivation) were also studied, and the methodological advantages of using computer technologies and electronic publications (EP) in solving them were substantiated.